Reimagining Art: The Influence of Artificial Intelligence on Digital Art Creation - Quiroz Rodriguez, Alejandro (2025)
This article examines how artificial intelligence (AI) is transforming digital image creation through advanced tools such as text transformation generators and style transfer technology. These tools open the door to artistic creativity and allow non-technical people to create visually appealing works using simple descriptions. The research addresses key topics such as authorship, creativity and ethical issues, and shows how artificial intelligence can augment human creativity by acting as a collaborator rather than a substitute. The results show that commercialized, easy-to-use AI tools significantly reduce barriers to entry, despite concerns about style homogeneity and technology dependence. The bottom line is that AI has a transformative role in digital art, but it also poses ethical and aesthetic challenges that must be addressed to ensure the diversity and originality of artistic expression.